Kesadaran Hukum Masyarakat dalam Paraktek Wakaf Produktif di Kecamatan Tompobulu Kabupaten Gowa - Munawir Nurum (STAI YAPIS Takalar, 2022)
Abstract Awareness Law Public is mark emerging base in self Man for shape and apply law, consciousness law important in life public To use for realize obedient society and obey to law. Likewise in Practice waqf , Article 43 paragraph (2) Republic of Indonesia Law no. 41 of 2004 concerning Endowment has entrust that treasure waqf should managed by Productive. However, Results study show that awareness law public related management waqf productive still belong to low. This thing could seen from endowment data there are 95 locations waqf, but not yet something is managed by productive. Thing this Because public still own paradigm waqf that is consumptive. By because that needed strategy special for build awareness law public in management waqf productive as socialization law waqf, or government To do strategy innovative as To do auction waqf. So that practice management waqf productive that could walking in the district Tompobulu, District Gowa. Keywords : Awareness Law , Waqf Productive.